2008
DOI: 10.1210/jc.2008-0568
|View full text |Cite|
|
Sign up to set email alerts
|

Variability in Thyroid-Stimulating Hormone Suppression by Human Chronic Gonadotropin during Early Pregnancy

Abstract: In early pregnancy, a woman's centile TSH level appears to determine susceptibility to the TSH being suppressed at any given hCG level, suggesting that hCG itself may be the primary analyte responsible for stimulating the thyroid gland. hCG affects lower centile TSH values disproportionately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 25 publications
6
41
0
3
Order By: Relevance
“…w e demonstrate elevated T4 she is really in state o f concluded that the induced elevation of T4 may b e hyperthyroidism but, it is the new physiological condition responsible for the morning sickness, nausea and and the metabolic regulation of pregnant women which vomiting of first-trimester of pregnancy, this finding is in realized and on that base, extra thyroxin requirement is agreement with many other studies in different part of requested, T4 is elevated, not for the sake o f the world (Al-Yatama et al, 2002;Caffrey, 2000; hyperthyroidism, but for the sake growing fetus demand Haddow et al, 2008;Sheehan, 2007). and the maternal new physiological conditions, therefore Laboratory assessment of thyroid function test the establishment of reference intervals and the during early stage of pregnancy and measurement of TSH, methodology of thyroid hormone measurements in each T4,T3,TBG, hCG and thyroid auto-antibodies, all help the region is a great importance (Dash et al, 2005).…”
Section: During Pregnancysupporting
confidence: 84%
“…w e demonstrate elevated T4 she is really in state o f concluded that the induced elevation of T4 may b e hyperthyroidism but, it is the new physiological condition responsible for the morning sickness, nausea and and the metabolic regulation of pregnant women which vomiting of first-trimester of pregnancy, this finding is in realized and on that base, extra thyroxin requirement is agreement with many other studies in different part of requested, T4 is elevated, not for the sake o f the world (Al-Yatama et al, 2002;Caffrey, 2000; hyperthyroidism, but for the sake growing fetus demand Haddow et al, 2008;Sheehan, 2007). and the maternal new physiological conditions, therefore Laboratory assessment of thyroid function test the establishment of reference intervals and the during early stage of pregnancy and measurement of TSH, methodology of thyroid hormone measurements in each T4,T3,TBG, hCG and thyroid auto-antibodies, all help the region is a great importance (Dash et al, 2005).…”
Section: During Pregnancysupporting
confidence: 84%
“…On the base of published studies, mostly from western countries, either the guidelines sponsored by the American Thyroid Association or by the American Endocrine Society suggested the following reference range: first trimester, 0.1 to 2.5 mU/l; second trimester, 0.2 to 3.0 mU/l; third trimester, 0.3 to 3.0-3.5 mU/l [6,9,15,16,17]. …”
Section: Diagnosis Of Sch In Pregnancymentioning
confidence: 99%
“…Available data derived from the literature indicate that in the first trimester the lower FT 4 limit (2.5th percentile) of the reference range, detected by immunoassay, is around 0.80 ng/dl (10.30 pmol/l) [16,17,27,28]. Given the uncertainty in FT 4 measurement during pregnancy, alternative strategies have also been suggested.…”
Section: Diagnosis Of Sch In Pregnancymentioning
confidence: 99%
“…These findings are in consistent with the findings of some researchers. 15,16 On the contrary, some other researchers had shown a lower level of serum FT 4 17 and higher level of serum TSH 18 in normal pregnant women during 1 st trimester in comparison to non pregnant women. 18% of normal pregnant women during 1 st trimester had TPO-Ab positivity in this study whereas, this finding was different in other countries 19 .…”
Section: Discussionmentioning
confidence: 89%